Analisis Kualitas Pelayanan Terhadap Kepuasan Konsumen PT. Pos Indonesia (PERSERO) Bantul Analysis Of Service Quality On Consumer Satisfaction PT. Pos Indonesia (PERSERO) Bantul - Dewi Triana; Dian Arifah Qurani (Sekolah Tinggi Ilmu Ekonomi Bisnis dan Perbankan, 2022)
The aim of this research is to invest in service quality and analyze PT. Pos Indonesia (PERSIAN) Bantul on customer satisfaction in terms of services provided by PT. Indonesian (PERSIAN) Bantul. The sample in this study are consumers of PT. Pos Indonesia (PERSIAN) Bantul, as many as 100 respondents. Data analysis used validity test, reliability test, classic hypothesis test and multiple linear regression test. The results showed that partially physical evidence had no significant effect on customer satisfaction, reliability had a significant effect on customer satisfaction, responsiveness had a significant effect on customer satisfaction, assurance had a significant effect on customer satisfaction, and empathy had a significant effect on customer satisfaction. Customer. While physical evidence, reliability, responsiveness, assurance, and empathy have a significant effect on PT. Pos Indonesia (PERSIAN) Bantul simultaneously.